Serum aldosterone and urine electrolytes dynamics in response to DASH diet intervention – An inpatient mechanistic study. Issue 1 (25th April 2022) - Bielopolski, Dana; Qureshi, Adam; Bentur, Ohad S.; Ronning, Andrea; Tobin, Jonathan N.; Kost, Rhonda
Abstract: Background: Dietary approach to stop hypertension (DASH) diet reduces blood pressure (BP) as effectively as one antihypertensive drug, yet its mechanism of action was never fully characterized. Methods: We designed a translational inpatient trial to elucidate the biological pathway leading from nutritional change, through hormonal response, reversal of urine electrolytes ratio, to BP reduction. Results: A single-center open-label interventional trial. Volunteers were admitted for 14 days, transitioning from an American-style diet to DASH diet. Vital signs, blood, and urine samples were collected daily. Participants completed two 24-hour ambulatory BP measurements (ABPM) and two 24-hour urine collections on days 1 and 10. Nine volunteers completed the protocol. During inpatient stay, serum aldosterone increased from day 0 (mean 8.3 ± 5.0) to day 5 (mean 17.8 ± 5.8) after intervention and decreased on day 11 (mean 11.5 ± 4.7) despite continuous exposure to the same diet ( p -value = 0.002). Urine electrolyte ratio ([Na]/[K]) decreased significantly from a mean of 3.5 to 1.16 on day 4 ( p < 0.001). BP by 24-hour ABPM decreased by a mean of 3.7 mmHg systolic BP and 2.3 mmHg diastolic BP from day 1 to 10. Conclusion: Shifting from a high-sodium/low-potassium diet to the opposite composition leads to aldosterone increase and paradoxical BP reduction. Urine electrolyte ratio reflects nutritional changes and should guide clinicians in assessing adherence to lifestyle modification.